2015
DOI: 10.13188/2377-9292.1000009
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-I Tax-Mediated Inactivation of Cell Cycle Checkpoints and DNA Repair Pathways Contribute to Cellular Transformation: “A Random Mutagenesis Model”

Abstract: To achieve cellular transformation, most oncogenic retroviruses use transduction by proto-oncogene capture or insertional mutagenesis, whereby provirus integration disrupts expression of tumor suppressors or proto-oncogenes. In contrast, the Human T-cell leukemia virus type 1 (HTLV-I) has been classified in a separate class referred to as “transactivating retroviruses”. Current views suggest that the viral encoded Tax protein transactivates expression of cellular genes leading to deregulated growth and transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…79 Given the constant expression of HBZ in all HTLV-1-infected cells, these data may provide a clue to explain the underlying mechanisms of p53 inactivation in ATL cells in the absence of Tax expression in majority of cases. 22 The Rb tumor suppressor gene is infrequently altered in structure 77,80 ; however, ;50% of ATL cases exhibit loss of Rb protein. 81 Additionally, low levels of Rb expression correlated with poor prognosis and shorter survival.…”
Section: Abnormalities In Specific Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Given the constant expression of HBZ in all HTLV-1-infected cells, these data may provide a clue to explain the underlying mechanisms of p53 inactivation in ATL cells in the absence of Tax expression in majority of cases. 22 The Rb tumor suppressor gene is infrequently altered in structure 77,80 ; however, ;50% of ATL cases exhibit loss of Rb protein. 81 Additionally, low levels of Rb expression correlated with poor prognosis and shorter survival.…”
Section: Abnormalities In Specific Genesmentioning
confidence: 99%
“…Therefore, Tax is considered to be a main viral factor involved in immortalization and transformation of the infected cells. [18][19][20][21][22] HTLV-1 also expresses a minus-strand RNA that can encode a basic leucine zipper factor, HTLV-1 bZIP factor (HBZ). 23,24 HBZ messenger RNA (mRNA) was shown to promote the proliferation of ATL cells.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the viral protein Tax is known to have substantial effects on DSB repair (117,118), it was important to understand how HBZ and Tax, together, affect the repair process. Interestingly, Tax has been shown to saturate the NHEJ repair pathway through two distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Johnson et al reported that Tax affects cell-cycle regulatory molecules, stabilizes, and inactivates the tumor suppressor p53 in HTLV-1 transformed cell lines by inducing hyperphosphorylation of p53 (19). Considering the “Random Mutagenesis transformation model” proposed to characterize the oncogenic activities of HTLV-1 (2), we could hypothesize that mutations linked to the UPS could have likely been produced in this case. Further research on gene–gene and gene–environment interactions of this oncogenic virus is need.…”
Section: Background and Discussionmentioning
confidence: 99%
“…Tax can inhibit multiple DNA repair pathways and stimulate incorrect DNA repair allowing accumulation of genetic mutations in the host genome and contributing to cellular transformation. This mechanism has recently been named by Nicot et al as “Random Mutagenesis Model” to characterize one of the oncogenic features of HTLV-1 (2). …”
Section: Introductionmentioning
confidence: 99%